2018
DOI: 10.12693/aphyspola.133.417
|View full text |Cite
|
Sign up to set email alerts
|

Collinear and Non-Collinear Configurations in Classical Geometrically Frustrated Ring-Shaped Systems

Abstract: Geometrically frustrated quantum spin systems, with competing antiferromagnetic couplings, show the Kahn degenerate frustration for some specific values of Heisenberg Hamiltonian parameters. It has been recently shown for rings with a defect bond and centered rings. In the case of classical counterparts of these systems, degenerated configurations with the lowest energy are present for the energy function parameter greater than a certain threshold. In these domains such configurations are planar but non-collin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Therefore, all of them exhibit the third type of frustration in this domain. Analogous behavior has been found in the classical and quantum counterparts of models discussed here [9,10,20]. However, in each of these cases systems behave in different ways when the ratio α is large enough.…”
Section: Discussionsupporting
confidence: 75%
“…Therefore, all of them exhibit the third type of frustration in this domain. Analogous behavior has been found in the classical and quantum counterparts of models discussed here [9,10,20]. However, in each of these cases systems behave in different ways when the ratio α is large enough.…”
Section: Discussionsupporting
confidence: 75%
“…Such a system is another example of models in which the collinear LEC is 'retained' when competing interactions are 'turned on' by a relatively weak antiferromagnetic coupling(s) [13,14,21]. This feature can be considered as the classical counterpart of the third type frustration according to the classification scheme recently proposed [8].…”
Section: Introductionmentioning
confidence: 99%
“…Note that higher degeneracy is not excluded and Schmidt [51] have provided an example of a classical spin system, when the lowest energy configuration can be realized in nonphysical four-dimensional space R 4 . For small systems some results have been obtained with simple calculus [55,59], but more general considerations need strictly proved properties, i.e., the results of this paper [see 60]. It is worth noting that for actually synthesized magnetic molecules [see, e.g., [61][62][63] there is needed analysis of some more general matrices (not regularly weighted graphs), e.g., alternating circulant matrices or arrow-bordered alternating circulant ones.…”
mentioning
confidence: 97%
“…They showed that for traceless dressed matrix (i.e., for j c j = 0) some physical quantities are "gauge independent". For fixed parameters of the system the eigenvalues of the dressed matrix, including its minimum eigenvalue λ min (c), depend on the gauge vector c. They proved that there exists max c∈R N λ min (c) and it equals, up to a constant factor, the minimum of the system energy E. The considerations performed in this paper give us a general solution of this problem for spins placed at vertices and the center of a regular n-gon with an even number n [see, e.g., [55][56][57][58]. The further physical analysis take into account also eigenvectors of the dressed matrix J, but this problem is out of scope here.…”
mentioning
confidence: 98%